Importance of Hydration and Surface Structure for Friction of Acrylamide Hydrogels - Simič, Rok; Yetkin, Melis; Zhang, Kaihuan; Spencer, Nicholas D. (Tribology letters, 2020)
To understand the dissipative mechanisms in soft hydrogel lubrication, polyacrylamide (PAAm) hydrogels with two distinct surface structures were examined under various contact conditions. The characteristic speed-dependent friction of the self-mated, crosslinked hydrogel surfaces could be explained by hydrodynamic shearing of a thin water layer between two rather impermeable bodies. On the other hand, the frictional response of brushy hydrogel surfaces is dependent on the contact conditions and the level of surface hydration. In a migrating contact, brushy hydrogels showed low, speed-independent friction ( µ ~ 0.01) likely due to a thick layer of shearing liquid trapped within the sparse surface network. In stationary contact, however, brushy hydrogel surfaces can partially exude water from the near-surface region over time, as shown by time-resolved Fourier-transform infrared (FTIR) spectroscopy. This is assumed to be reflected in a friction increase over time. Interfacial shearing appears to shorten the characteristic exudation times compared to those observed under static loading. Once fluid has been exuded, brushy surfaces were shown to reach similar friction values as their crosslinked analogs. The results thus indicate that the dominating dissipation mechanism during sliding at low contact pressures is shearing of the interfacial liquid film, rather than poro-elastic dissipation within the bulk. Maintenance of surface hydration is therefore crucial, in order to take advantage of the low friction of such systems.